Biblia i nauka. Siedem refleksji inspirowanych myślą ks. Michała Hellera - Majewski, Marcin (Collectanea Theologica, 2018)
The aim of the article is to show some areas where the results of exegesis and biblical theology should be confronted with the latest discoveries of science on the world, nature, evolution, the human being, the brain, free will, psychology and morality. The author compares, shows difficulties arising from, and attempts to reconcile Christian anthropology with the image of man that emerges from well-established scientific truths. This paper is an introduction and an invitation to a discussion on this topic.